INTRODUKSI KAMPUNG ANGGUR SEBAGAI UPAYA PENINGKATAN KONTRIBUSI SUMBER DAYA MANUSIA DALAM RANGKA OPTIMALISASI EKOWISATA KAWASAN PEDESTRIAN CODE GUMREGET - saputro, wahyu adhi saputro; Ali Hasyim Al Rosyid; Liana Fatma Leslie Pratiwi; Irene kartika Eka Wijayanti; Yunita Firdha Kyswantoro (Jurnal Jarlit, 2024)
The Yogyakarta City government's efforts to minimize slum areas by realizing road widening on the banks of the Code River. This initiative was realized by creating the Pedestrian Code Gumreget (PCG). The aim is to improve the standard of living of people close to the river. The potential possessed by PCG, especially in the lower gemblakan area, is still accompanied by several existing problems. The first problem is the tourism potential that can still be optimized by adding new tourism items that can attract tourists to visit. The second problem is that the good tourism potential has not been supported by digital marketing in promotional efforts. This study uses a descriptive qualitative method approach. Data analysis techniques are preceded by compiling, preparing data, reading the data owned and analyzing data with a coding process ending with a description. In this Grape Village Introduction study, there are five activities that will be carried out, namely strengthening institutions, making processed grape products, cultivating grapes, digital marketing, social engineering and benchmarking. The results of the study showed that KWT GEMARI PCG succeeded in utilizing local potential by developing processed grape-based products, mastering grape cultivation techniques to grafting, and utilizing digital marketing to expand the market. The conclusion of this study emphasizes the importance of empowering human resources in supporting ecotourism aspirations in Kampung Anggur, and shows that this initiative has great potential to improve community welfare through sustainable ecotourism.